The cruise shipping industry in the corporate mergers and overpanamax eras. A comparison with the container shipping industry - Jacques Charlier (Belgeo)
After container shipping, the cruise shipping industry has entered recently into the overpanamax era, in a typical quest for economies of scale, at the same time as it was searching for economies of scope, including through corporate mergers. To some extent, the evolution has been indeed similar, but there are also some major differences.On the one hand, it is obvious that building always larger ships, from infrapanamax to panamax and finally to overpanamax standards, has brought significant savings in building and operational cost per lower berth for the cruise industry as per TEU in container shipping. And it is also obvious that, besides these economies of scale, building quite long series of ships for the same line or for sister lines has also been an attractive option for the cruise lines. Moreover, in an another search for economies of scope, some cruise lines did not only expand organically, but also externally, again as for container shipping, buying some of their competitors and integrating their ships into their fleet after harmonizing the products. Or alternatively, they may have kept the existing brands, because they had either a well-established global reputation or a strong regional basis. This has led to the formation of a few major groups whose spatial reach is now global, the largest of which is by far Carnival Corporation/plc, born in 2003 from the merger of Carnival Corporation and Princess Cruises.But on the other hand, there are significant differences between the two industries, one of which being that the dominance of Carnival Corporation/plc is much more overwhelming in the cruise industry than that, in container shipping, of the AP Moller group (itself incorporating two of the previous industry leaders). Moreover, cruise ships are not standardized products as containerships are. The most important difference is that same hull can be used to build similar ships for brands of the same qualitative level, or even quite different ships of different qualitative levels within the same cruise lines’ group. Another major difference is that the cruise industry is still dominated, by far, by American or European-based groups or lines, and that most cruise ships have been and are being built at European yards.